RETROSPECTIVE STUDY ON ASSESSMENT OF FACTORS ASSOCIATED WITH HYSTERECTOMIZED PATIENTS - Daniel Varughese, Jilu; A S K, Sankara (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The study was carried out to determine the age pattern, indications, risk factors, co-morbid conditions, type of surgery, and the associated complications of hysterectomized patients. Methods: A cross-sectional, retrospective study was done over a period of 8-month. A total of 150 hysterectomies were documented. Results: All data collected were analyzed and in this 111 hysterectomies (74%) were done by vaginal route and 39 (26%) done abdominally. In which, 50.60% hysterectomized patients were in the age group 40-50 years and 32% patients were in 50-60 years. Out 111 vaginal hysterectomy (VH), 79 are laparoscopic-assisted VH. Fibroid (33.33%) and dysfunctional uterine bleeding (DUB) (17%) were the most common indication. Complications were injuries to the bladder in 5 patients, 4 wound sepsis, 2 chronic cervicitis, 1 menopausal symptoms, 1 thrombocytosis, bilateral mild hydronephrosisin 1, and right ovarian cyst in 1 patient. This study also recorded the common co-morbid medical conditions in women undergoing hysterectomies include diabetes mellitus, 30.66%; hypertension, 23.33%; hypothyroid, 19.33%; dyslipidemia, 12%. Conclusion: The present study shows that the most common method performed is VH. Fibroid and DUB are very common indications for undergoing hysterectomy; of these, most of the hysterectomized patients were in the age group of 40-50 years. Laparoscopic hysterectomy may be an alternative to abdominal hysterectomy for those patients in whom a VH is not indicated. All women should be carefully evaluated before surgery, and its route is decided. Keywords: Hysterectomy, Fibroid, Dysfunctional uterine bleeding, Complications.